Reflexiones acerca de los derechos del enfermo mental - Álvarez, Gloria Cielo (Revista Estomatología, 1999)
This article includes a description about how society has perceived the mentally ill person, his/ her fundamental rights as human being and as patient, and the need to protect his/her physical, psychological, and social integrity.